Strategi Guru IPS dalam Pembelajaran Berbasis Boarding School pada Siswa Kelas VII di MTs Darul Hikmah Tawangsari Tulungagung - Mohammad Taufik Rifai; Jani Jani (STIKes Ibnu Sina Ajibarang, 2025)
This research is motivated by the importance of education as a basic right of the nation's children that continues to experience innovation, including in the school model based on boarding school. The focus of the research is social studies learning at MTs Darul Hikmah Tulungagung which implements the boarding system. The purpose of this study was to determine teacher strategies, implementation, and obstacles in social studies learning in this environment. The study used a qualitative approach with a case study type, and data was collected through observation, interviews, and documentation. The results of the study showed that the effectiveness of social studies learning was influenced by the density of institutional activities, lack of mastery of the material by teachers, and dualism of the curriculum. Efforts made include improving teacher discipline, utilizing audio-visual media, and linking material to current issues. The advantages of the boarding school system are that students become more independent, have high social awareness, and obtain general and religious education in a balanced manner. This finding implies the need for improvements in learning strategies and time management so that the boarding school system can run more optimally in supporting the achievement of social studies learning.